La tourbe, ses propriétés et ses utilisations - Lavigueur, Jacques (Assurances, 1983)
The writer's comments seem to us to be worthy of interest because they describe a material with many uses which is found throughout Canada. We believe that most of our readers will be unaware of its origin and its characteristics. We believe they will be interested to learn more, by reading this excellent article by Mr. Jacques Lavigueur.